Case report: Turcot syndrome type 2 in a developing country within the Caribbean - Daniel-Abdool, Melissa; Griffith, Brandon; Bartels, Ute; Bodkyn, Curt; Dindial, Kevon (Frontiers in Oncology, 2024)
Medulloblastoma is the most common malignant paediatric brain tumour and has been linked to known cancer predisposition syndromes. We report a case of medulloblastoma of a 12-year-old Indo-Trinidadian female with a strong family history of colorectal carcinoma. In collaboration with the SickKids-Caribbean Initiative (SCI), her tumour was confirmed to be a WHO grade 4 medulloblastoma -Wnt subtype. Genetic testing further confirmed the presence of a pathogenic APC gene variant (c.3183_3187del (p.Gln1062*)) which led to a diagnosis of Turcot syndrome type 2. The index patient received multimodal therapy which included surgery, radiation and chemotherapy and is currently post end-of-treatment and in remission. This case report aims to highlight the complexity of diseases and the need for expertise in identifying them in low-and-middle income countries, the need for access to specialized testing and the benefits of collaborating between low-and-middle income and high-income countries when managing complex oncology patients.